Landfill mining report_2016.pdf - Canopoli, Luisa; Wagland, Stuart T.; Coulon, Frederic (Cranfield University, 2017)
An era of rising consumption has led to resource scarcity across major industries. One way to overcome this challenge and ascertain future supply of resources is recovery of landfilled material. This so-called landfilled mining may valorise previously discarded material streams for a number of purposes and contribute to a circular economy. Across England and Wales, there are more than 20,000 landfill sites of which 90% have been closed before 1996. Besides the general belief that valuable resources can be found within landfills, mining the waste has a number of additional benefits. One stems from the fact that they often lack modern environmental protection technology, which may lead to negative environmental and health impacts. The combination of these facts poses an interesting opportunity for combined resource-recovery and remediation strategies. The report at hand is in place to assess viability and feasibility of landfill mining processes across England and Wales in a step-wise approach
Keywords: landfill sites'; 'Mining engineering'; 'Raw materials'; 'rare earth elements'; 'Environmental Science'; 'Civil Geotechnical Engineering'; 'Environmental Engineering not elsewhere classified'; 'Environmental Technologies'